1996
DOI: 10.4012/dmj.15.91
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Magnetically Attractive Experimental Resin Composites

Abstract: SUS444 stainless steel filled chemically cured resin composites that can attract magnet were fabricated. The filler was treated with various concentrations of silane. The experimental composite was easy to handle and showed a good shelf life. The maximal properties obtained are as follows; The attraction force to a magnetic attachment was 1/3-1/4 lower than the commercially available magnet-keeper system for dental magnetic attachment. Flexural strength and Knoop hardness of the composite were 76MPa (7.7kgf/ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Fig. 6 shows the iso-value curves of the elastic modulus with the changes in 4-META concentration and metal particle content, which was drawn using the equation (2). As shown in Fig.…”
Section: Flexural Strength and Elastic Modulusmentioning
confidence: 99%
“…Fig. 6 shows the iso-value curves of the elastic modulus with the changes in 4-META concentration and metal particle content, which was drawn using the equation (2). As shown in Fig.…”
Section: Flexural Strength and Elastic Modulusmentioning
confidence: 99%
“…Endo et al 4) also reported that the breakdown potential of ferric stainless steels increased and the total amount of released metal ions decreased linearly with increase in the sum of Cr and Mo contents. As for experimental magnetic resin composites, immersion tests have been conducted by Hirano et al using SUS444 (18 Cr, 2 Mo) 7) and SUS446 (26.7 Cr, 0 Mo) 9) fillers. The sums of the Cr and Mo contents of SUS444 and SUS446 were 20 and 26.7 , respectively, and the amount of eluted metals from the resin composite containing SUS446 was reported to be less than that from the resin composite containing SUS444 9) .…”
Section: Discussionmentioning
confidence: 99%
“…As for the obtained elastic moduli, they were equal to or higher than those of commercial hybrid composite resins 20) . Although the attraction force between the experimental soft magnetic resin composites and a commercial hard magnet was not measured because of the difficulty in applying the method described in a report 7) , specimens for the flexural test were attracted very well by a commercial hard magnet. Based on this observation, it could be said that this soft magnetic resin composite was thought to be promising in terms of magnetic attractive force.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations